Looking Back and Moving Forward: A History and Discussion of Privately Practising Midwives in Western Australia - Davison, Clare Louise (Curtin University, 2019)
The aim of this historical narrative research study was to fill a gap in the literature by investigating, analysing and describing the history of privately practising midwives in Western Australia (WA) from colonisation to the present day (approximately 1830-2018). This study embedded within a naturalistic, feminist paradigm analysed oral history interviews from fifteen midwives and three doctors, and archival documents to reconstruct the history, and explore the experiences of privately practising midwives in WA.